2021
DOI: 10.22435/bpk.v49i3.4620
|View full text |Cite
|
Sign up to set email alerts
|

Situasi Filariasis Limfatik di Daerah Pasca Pemberian Obat Pencegahan Massal (POPM) dan Pasca Eliminasi di Kabupaten Tanjung Jabung Timur dan Belitung

Abstract: East Tanjung Jabung Regency, Jambi did not pass in the Pre-Transmission Assessment Survey (Pre-TAS) in 2017, while Belitung, Bangka Belitung has a microfilaria rate (Mf rate) >1% even though it has passed TAS 1,2, and 3. The purpose of this study is to identify the program implementation control of lymphatic filariasis in East Tanjung Jabung Regency and Belitung Regency. The research was conducted in four villages, namely of Rantau Rasau 2, Nibung Putih (East Tanjung Jabung), Lasar, and Suak Gual (Belitung)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…17 A study conducted by Santoso et al had shown that 366 people (52.2%) in Bangka Belitung and 335 people (47.8%) in Jambi stated that there was enlargement of the hands and feet as a result of filariasis. 20 In Table IV, it is known that the majority of respondents in the two villages of West Kotawaringin Regency who had good In Table IV, it is also known that there were 99 respondents (41.8%) with poor knowledge and 79 respondents with poor attitude (33.3%). In result to this, it is still necessary to increase health promotion in the form of delivering health information about filariasis.…”
Section: Resultsmentioning
confidence: 99%
“…17 A study conducted by Santoso et al had shown that 366 people (52.2%) in Bangka Belitung and 335 people (47.8%) in Jambi stated that there was enlargement of the hands and feet as a result of filariasis. 20 In Table IV, it is known that the majority of respondents in the two villages of West Kotawaringin Regency who had good In Table IV, it is also known that there were 99 respondents (41.8%) with poor knowledge and 79 respondents with poor attitude (33.3%). In result to this, it is still necessary to increase health promotion in the form of delivering health information about filariasis.…”
Section: Resultsmentioning
confidence: 99%
“…Tingkat pengetahuan petugas kesehatan di Puskesmas di wilayah Belitung juga masih rendah hal ini juga berdampak pada tingkat pengetahuan masyarakat yang juga rendah. 15 Kegiatan pengendalian filariasis di Kabupaten Belitung sejak tahun 2017 hingga saat ini menunjukkan tidak adanya kegiatan rutin. Hal ini karena filariasis sudah tidak dianggap sebagai masalah kesehatan lagi di wilayah ini.…”
Section: Peran Petugas Dalam Penanganan Limfatik Filariasisunclassified